Variation in timely surgery for severe open tibial fractures by time and place of presentation in England from 2012 to 2019 <subtitle>a cohort study using data collected nationally by the Trauma Audit and Research Network</subtitle> - Anjali Shah; Andrew Judge; Xavier L. Griffin (Bone & Joint Open, 2022)
AimsSeveral studies have reported that patients presenting during the evening or weekend have poorer quality healthcare. Our objective was to examine how timely surgery for patients with severe open tibial fracture varies by day and time of presentation and by type of hospital. This cohort study included patients with severe open tibial fractures from the Trauma Audit and Research Network (TARN).MethodsProvision of prompt surgery (debridement within 12 hours and soft-tissue coverage in 72 hours) was examined, using multivariate logistic regression to derive adjusted risk ratios (RRs). Time was categorized into three eight-hour intervals for each day of the week. The models were adjusted for treatment in a major trauma centre (MTC), sex, age, year of presentation, injury severity score, injury mechanism, and number of operations each patient received.ResultsWe studied 8,258 patients from 175 hospitals. Patients presenting during the day (08:00 to 15:59; risk ratio (RR) 1.11, 95% confidence interval (CI) 1.02 to 1.20) were more likely to receive debridement within 12 hours, and patients presenting at night (16:00 to 23:59; RR 0.56, 95% CI 0.51 to 0.62) were less likely to achieve the target; triage to a MTC had no effect. Day of presentation was associated with soft-tissue coverage within 72 hours; patients presenting on a Thursday or Friday being less likely to receive this surgery within 72 hours (Thursday RR 0.88, 95% CI 0.81 to 0.97; Friday RR 0.89, 95% CI 0.81 to 0.98), and the standard less likely to be achieved for those treated in ‘non-MTC’ hospitals (RR 0.76, 95% CI 0.70 to 0.82).ConclusionVariations in care were observed for timely surgery for severe open tibial fractures with debridement surgery affected by time of presentation and soft-tissue coverage affected by day of presentation and type of hospital. The variation is unwarranted and highlights that there are opportunities to substantially improve the delivery and quality of care for patients with severe open tibial fracture.Cite this article: Bone Jt Open 2022;3(12):941–952.